Phylogenomic Based Comparative Studies on Indian and American Commensal Staphylococcus epidermidis Isolates - Sharma, Shikha; Chaudhry, Vasvi; Kumar, Sanjeet; Patil, Prabhu B. (Frontiers in Microbiology, 2018)
Staphylococcus epidermidis is a prominent commensal member of human skin microbiome and an emerging nosocomial pathogen, making it a good model organism to provide genomic insights, correlating its transition between commensalism and pathogenicity. While there are numerous studies to understand differences in commensal and pathogenic isolates, systematic efforts to understand variation and evolutionary pattern in multiple strains isolated from healthy individuals are lacking. In the present study, using whole genome sequencing and analysis, we report presence of diverse lineages of S. epidermidis isolates in healthy individuals from two geographically diverse locations of India and North America. Further, there is distinct pattern in the distribution of candidate gene(s) for pathogenicity and commensalism. The pattern is not only reflected in lineages but is also based on geographic origin of the isolates. This is evident by the fact that North American isolates under this study are more genomically dynamic and harbor pathogenicity markers in higher frequency. On the other hand, isolates of Indian origin are less genomically dynamic, harbor less pathogenicity marker genes and possess two unique antimicrobial peptide gene clusters. This study provides a basis to understand the nature of selection pressure in a key human skin commensal bacterium with implications in its management as an opportunistic pathogen.